Prevention and Control of African Swine Fever in the Smallholder Pig Value Chain in Northern Uganda: Thematic Analysis of Stakeholders' Perceptions - Aliro, T.; Chenais, E.; Odongo, W.; Okello, D. M.; Masembe, C.; Ståhl, K. (Frontiers in Veterinary Science, 2022)
African swine fever (ASF) is endemic in Uganda and considered a major constraint to pig production. In the absence of a vaccine, biosecurity is key for ASF prevention and control. To improve prevention and control on farm and community level there is need for more knowledge on current application of biosecurity practices, and better understanding of how pig value chain actors perceive prevention and control. To achieve this, a qualitative interview study involving focus group discussions (FGD) was conducted with actors from the smallholder pig value chain in northern Uganda. Six villages were purposively selected based on previous outbreaks of ASF, preliminary perceived willingness to control ASF, and the representation of several different value chain actors in the village. Results indicated that biosecurity practices such as basic hygiene routines including safe carcass handling, minimising direct and indirect contacts between pigs or between pigs and people, trade restrictions and sharing of disease information were implemented in some of the villages. Thematic analysis based on grounded theory revealed six categories of data relating to ASF prevention and control. Together these categories form a logical framework including both enablers and hindrances for ASF prevention and control. In summary participants mostly had positive perceptions of ASF biosecurity, describing measures as effective. Participants further possessed knowledge of ASF and its transmission, some of which was in line with known scientific knowledge and some not. Nevertheless, participants were hindered from preventing and controlling ASF due to biosecurity costs and a need to prioritize family livelihood over disease transmission risks, incompatibility of current biosecurity practices with local culture, traditions and social contexts and finally lack of access to veterinarians or, occasionally, low-quality veterinary services. The constraints could be addressed by applying participatory processes in designing biosecurity measures to ensure better adaptation to local cultural and social contexts.